Student Unrest in Public Universities in Kenya: The Nexus between Principles of Governance and Student Leadership - Washington Okeyo (European Scientific Journal, ESJ, 2017)
Student unrest has been a major problem in Kenya for the government, public universities, the community, society, and even students themselves for several decades. However, the student leaders, majority of who are undergraduates in their late teens to early twenties, lack governance and leadership skills and experience. This study focused on principles of governance and leadership among student leaders in public universities. The study was anchored on positivist research philosophy and adopted a cross sectional design. The target population was all the 35 public universities in Kenya and data was collected from 70 student chairpersons and their deputies. Data was mainly collected from primary source using structured questionnaire and analyzed using descriptive and regression analysis. The study established that student leaders exhibited both performance and accountability principles of governance albeit weakly. The study however found no significant relationship between and student leadership and governance principles of legitimacy and voice; direction; and fairness. This study thus concludes that when student leaders are articulating their fellow students’ issues, the leaders are guided by responsiveness, effectiveness, efficiency, transparency, and information flow. The leaders however lack appreciation for rule of law; equity; consensus orientation and mediation; as well as long-term strategic vision for the student body. The study therefore recommends that public universities should immediately train all incumbent student leaders on leadership concepts and principles of governance. However as a long-term measure, universities should introduce curriculums on principles of governance and leadership concepts contextualized to undergraduate students’ area of study.